Attitudes Toward Older People Among Nursing Students in Southeast Asia: A Narrative Review - Suyasa, I Gede Putu Darma; Agustini, Ni Luh Putu Inca Buntari; Sutini, Ni Kadek; Israfil, Israfil; Rittiruang, Amonwan (STIKES Adi Husada, 2025)
The rapid growth of the older population worldwide has had significant consequences in the health care system, especially in preparing prospective nurses as health workers with positive attitudes towards older people. Unfortunately, students' attitudes have been reported to vary from positive attitudes to indications of ageism towards the older age group. This study aimed to identify and describe current findings regarding nursing students' attitudes toward older people in Southeast Asian countries. This study was conducted using a narrative review approach. The literature was sourced from international databases: PubMed, Science Direct, EBSCOhost, and ProQuest. Keywords included